Analysis of the screening accuracy of a linear vibrating screen with a multi-layer screen mesh - Yan, Hongwei (Strojniški vestnik, 2020)
This paper investigates the screening characteristics of the multi-layer vibrating screens. A portable linear screen with a three-layer screen mesh and the vibrating screening experimental platform were designed and simulated. Based on the discrete element method (DEM), the influences of the motor excitation frequency, the pulverized coal mass flow rate, and the shape of the particles on the screening accuracy of each layer of the screen and the total energy contained in the particles were analysed. The simulation analysis found that, during the vibration screening process, with the increase of the frequency of motor excitation, the screening accuracy of each screen layers increased first and then decreased. The ratio of the sieving accuracy of the first screen and the third screen is reduced first and then increased. The energy contained in the particles gradually increases. With the increased pulverized coal mass flow rate, the screening accuracy of each layer gradually decreased, while the ratio of the screening accuracy of the first layer to that of the third layer gradually increased. The energy contained in the particles gradually decreases. Similarly, the increased percentage of non-spherical particles generated slightly decreased screening accuracy and an increased ratio of the screening accuracy of the first and third screens. The particles also contain much less energy than spherical particles do. A simulation was carried out on the vibrating screening experimental platform with screening materials such as soybeans and red beans. The experimental results matched the discrete element simulation. The screening accuracy was proved to be higher when the excitation frequency lay in 18 Hz to 20 Hz, and the particles mass flow rate stayed below 0.4 kg/s. This study demonstrated that changing the shape of particles is a practical way of managing real screening work. It also provided a theoretical basis and reference for the design and applications of multi-layer vibrating screens.
Keywords: discrete element method; excitation frequency; masni pretok; mass flow rate; metoda diskretnih elementov; natančnost sejanja; oblika delcev; particle shape; screening accuracy; vibracijsko sito; vibration sieve; vzbujalna frekvenca